The Mediating Role of New Media Engagement in This Digital Age - Yujie, Zhang; Al Imran Yasin, Megat; Alsagoff, Syed Agil Bin Shekh; Hoon, Ang Lay (Frontiers in Public Health, 2022)
Web-related technologies, such as social networking sites, blogs, online social media networking, and other forms of communication technology, are included in New Media Technologies. They are used to connecting with people and sharing their health status with others using current communication technologies. Audiences consuming public health news at anytime, anywhere, and on any device are pushing a news organization's digital transformation to a mobile-first approach in the current digital era. Mobile phones, particularly social media, impact young people's news. The key objective of this article is to investigate the mediating role of the digital age and modern media engagement in the pandemic COVID-19 period. In addition, this research highlights the idea of new media and uses the features of modern media technologies to connect public health sector people in the COVID-19 Crisis. To achieve the aforementioned aims, the researcher performs a questionnaire survey to demonstrate modern media involvement and big data analysis between the instructions given to the newsroom in this digital era and people's attitudes on social media. According to the study's findings, in the COVID-19 situation, the majority of people in the digital era have a favorable attitude toward modern media technologies in the health sector. In this day and age, many assume that social media is secure and less harmful for all people in terms of communication and contact.